The genus navicula sensu stricto in the upper lerma basin, México. I - Segura García, Virginia (2010)
In order to characterize and analyze the distribution of species of the genus Navicula sensu stricto in the Lerma River and its tributaries, biannual samplings (wet and dry seasons) for the period 2003 to 2005 were made at eleven locations in the Upper Lerma basin, central-western Mexico. Twenty-one species of Navicula Bory, were identified, of which fourteen represent new records for Mexico and five were new to the study area. Most of the species of Navicula s. str. observed in the study area are tolerant to high contents of organic matter, which is incorporated into the aquatic ecosystems as a product of agricultural and industrial activities and from deficiently treated municipal discharges of cities and towns present in the study area at the sites most affected by these activities. Cosmopolitan species with broad tolerances to organic pollution and eutrophic conditions, such as Navicula antonii, N. germainii, N. perminuta, N. rostellata and N. erifuga were present throughout the year. N. tripunctata and N. veneta, widely reported as tolerant to pollution from industrial activities in other regions of the world, were present at the sites most affected by these activities.